2009
DOI: 10.1002/ajp.20783
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites of the chimpanzee population introduced onto Rubondo Island National Park, Tanzania

Abstract: The release of any species into a novel environment can evoke transmission of parasites that do not normally parasitize the host as well as potentially introducing new parasites into the environment. Species introductions potentially incur such risks, yet little is currently known about the parasite fauna of introduced primate species over the long term. We describe the results of long-term monitoring of the intestinal parasite fauna of an unprovisioned, reproducing population of chimpanzees introduced 40 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 50 publications
3
28
1
Order By: Relevance
“…The rate of global strongylid infection was 85.1 %. This rate was significantly higher than the 10.9 to 41.3 % strongylid prevalence in wild Pan troglodytes schweinfurthii populations in Rubondo Island National Park, Tanzania (Petrášová et al 2010; Petrzelková et al 2010), 19.53 % prevalence in wild Pan troglodytes verus population in Fongoli, Senegal, (Howells et al 2011) and 13.04 % prevalence found in captive Pan troglodytes elliotii from Calabar, Nigeria (Mbaya and Udendeye 2011). However, this rate of infection was similar to what was found in Pan troglodytes schweinfurthii populations of Gombe National Park, Tanzania (Gillespie et al 2010), and Kibale National Park, Uganda (Krief et al 2005; Muehlenbein 2005), with a strongylid prevalence ranging from 74.32 up to 100 %.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The rate of global strongylid infection was 85.1 %. This rate was significantly higher than the 10.9 to 41.3 % strongylid prevalence in wild Pan troglodytes schweinfurthii populations in Rubondo Island National Park, Tanzania (Petrášová et al 2010; Petrzelková et al 2010), 19.53 % prevalence in wild Pan troglodytes verus population in Fongoli, Senegal, (Howells et al 2011) and 13.04 % prevalence found in captive Pan troglodytes elliotii from Calabar, Nigeria (Mbaya and Udendeye 2011). However, this rate of infection was similar to what was found in Pan troglodytes schweinfurthii populations of Gombe National Park, Tanzania (Gillespie et al 2010), and Kibale National Park, Uganda (Krief et al 2005; Muehlenbein 2005), with a strongylid prevalence ranging from 74.32 up to 100 %.…”
Section: Discussionmentioning
confidence: 69%
“…Concerning the other helminth infections ( Ascaris , Trichuris , Abbreviata , Capillaria , Enterobius , Bertiella , Fluke and Hymenolepis ), the prevalence was low and ranged from 0.9 to 4.5 %, depending on the species, and was similar to or below the average rate of infection found in other chimpanzee communities in Tanzania, Nigeria, Uganda, and Central African Republic (Lilly et al 2002; Krief et al 2003; Gillespie et al 2010; Howells et al 2011; Petrášová et al 2010; Petrzelková et al 2010; Mbaya and Udendeye 2011). …”
Section: Discussionmentioning
confidence: 70%
“…The apparent lack of seasonality in strongylids of Rubondo chimpanzees and guerezas might be caused by their lower prevalence in comparison to vervets. Petrželková et al (2006Petrželková et al ( , 2010 previously reported Anatrichosoma sp. and Subulura sp.…”
Section: Discussionmentioning
confidence: 97%
“…was reported to be associated with increased host density and frequency of contact between uninfected and infected hosts in the group (Gillespie et al 2005b). Petrželková et al (2006Petrželková et al ( , 2010 identified the spirurids occurring in Rubondo chimpanzees as Protospirura muricola based on adult morphology. We found morphologically identical spirurid eggs also in guerezas and vervets and we suggest that all primates at Rubondo probably harbor the same species of spirurid.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation